Post-operative Corona Radiata Infarct in a High-flow EC-IC Bypass: Report of Unusual Complication - Chowdhury, Forhad H.; Haque, Mohammod Raziul (Indian Journal of Neurosurgery, 2022)
Long insular artery (LIA) infarct can occur after insular glioma surgery. LIA infarct after extracranial-intracranial (EC-IC) bypass is very rare, and so far, it is not reported in EC-IC bypass. Here, we report a case of high-flow EC-IC bypass, where postoperatively, the patient developed isolated LIA infarct. A 65-year-old female presented with recurrent severe headache along with altered sensorium. Computed tomography (CT) scan and CT angiography (CTA) of the brain showed ruptured large left internal carotid artery (ICA) fusiform aneurysm. She underwent left-sided, high-flow EC-IC bypass involving upper trunk of left middle cerebral artery (MCA) and ICA ligation at neck at its origin. Postoperatively, the patient developed right sided hemiplegia. Postoperative MRI of the brain showed left-sided external capsular infarct, extending up to the corona radiata resulted from LIA infarct. By the end of 6 months after operation, she could walk with support but her left upper limb remained more severely affected and magnetic resonance angiogram (MRA) showed almost disappearance of aneurysm with functioning bypass.
Keywords: long insular artery; infarct; EC-IC bypass; ICA aneurysm; corona radiata infarct